The Main Muscle Groups and their Functions - Alimqul o'g'li, Andaboyev Akbar; Zavqiyevna, Sattarova Sabina (Journal of Science in Medicine and Life, 2025)
Myology (Latin myologia, from Greek: mys - muscle and lós "study, science") is a science that includes information about the muscular system, its structure, development, function, comparative anatomy and anomalies. In a narrow sense, myology describes the structure of skeletal muscles and, together with osteology and syndesmology, constitutes the study of the musculoskeletal system in anatomy [1].